Investigating Pure Bundling in Japan’s Electricity Procurement Auctions - Suzuki, Ayako (Mathematics (Basel), 2021)
This study investigates the effect of bundling contracts on electricity procurement auctions in Tokyo. We conduct structural estimations that include elements of asymmetry between the incumbent and the new entrant firms and that endogenize the participation of bidders, and investigate the effect of bundling on the costs of firms, competition between the incumbent and the new firms, and auction outcomes. The results first confirm that bundling contracts raises the cost of firms, increases the asymmetry between incumbent and new firms and helps exclude new firms from auctions. We find the negative effect increasing the costs of firms is somewhat mitigated by a larger scale of bundling, but that the negative effect on participation is scarcely offset by scale. The payment of the auctioneer may decline if bundling results in a large-sized auction, but the profit of the winner is always found to be lower in bundled auctions, presumably because firms bid more aggressively owing to the smaller dispersion of the opponents’ cost distributions.